Genome-wide identification and expression analysis of soybean bHLH transcription factor and its molecular mechanism on grain protein synthesis - Wu, Nan; Jiang, Tao; Feng, Yongqi; Yuan, Minghao (Frontiers in Plant Science, 2025)
IntroductionSoybean seeds have a protein content of about 40% and are widely used due to their unique nutritional value. Research has found that drought and nitrogen fertilizer environments are conducive to the formation and accumulation of grain protein. Nitrogen is an essential element for soybean growth and development, and is converted into grain protein through a series of pathways such as the soybean root nodule system. The earliest report on the regulation of nodulation by bHLH transcription factors in leguminous plants was in 2011, but the network regulatory mechanism of their involvement in soybean protein synthesis is still unclear.MethodsThis study we use BLASTP and HMMER to identified 296 soybean GmbHLH genes through whole-genome identification and systematic analysis and is classified into 29 subfamilies, by comprehensively analyzing complex biological issues such as gene structure, function, interactions, and regulatory networks.ResultsThis study explores the life processes of soybean growth, development, metabolism, and resistance to adversity.The non-synonymous substitution rate/synonymous substitution rate (Ka/Ks) analysis indicates that most of the homologous genes have undergone purifying selection (Ka/Ks << 1). Cis-acting element analysis of the promoter revealed that this gene family plays an important role in stress response, growth and development, hormone regulation, and other processes. RNA-seq data and qRT-PCR experiments indicated that GmbHLH genes were diversely expressed in different organs/tissues, and many GmbHLH genes were found to be differentially expressed under salt, and drought stresses, suggesting their critical role in soybean resistance to abiotic stress.DiscussionThe GmbHLH98 gene(LOC100778376), which is highly expressed under both drought and salt stress, was selected for functional validation. Molecular and agronomic trait analyses of positive transgenic offspring showed that the protein content of soybean seeds increased by 36.8%, indicating that drought and salt conditions promote protein synthesis. This study provides a theoretical basis for exploring the synergistic regulation of drought and salt response and protein synthesis by GmbHLH98 in the future.These results provide fundamental information about the soybean bHLH genes and will aid in their further functional elucidation and exploitation.